Aplicación de métodos deterministas para la planificación de la expansión de la red de transmisión en Ecuador - Lata Gualancañay, Alex Dario (2023)
In this research project, the modeling of deterministic methods for transmission expansion planning (PET) was developed, with the purpose of evaluating the best planning model, to satisfy the progressive increase suffered by electricity demand in transmission networks. , and to be able to transport the respective amount of electrical energy projected to a respective determined horizon of study time 2022 - 2032.